Kinerja Karyawan Ditinjau Dari Lingkungan Kerja dan Motivasi Berpretasi Pada CV. Cendana Megah Santosa Kecamatan Purwodadi Kabupaten Grobogan Tahun 2015 - Ristiani, Atik, Dr. Sabar Narimo, MM, M.Pd (2015)
The purpose of this study was to describe: 1) The work environment on employee performance CV. Magnificent Santosa 2015 sandalwood, 2) Achievement motivation on employee performance CV. Magnificent sandalwood Santosa 2015, 3) The work and achievement motivation on employee performance CV. Magnificent Santosa 2015 sandalwood. The method used in this research is descriptive quantitative method. The data in this study was obtained from data from the questionnaire. Data collected by using a filling questionnaires, observation, and documentation. The results showed: 1) The results of multiple linear regression analysis obtained by the working environment of 0.342, 0.245 of achievement motivation, this proves that the work environment variables and achievement motivation have an influence on the performance of employees at the company CV. Magnificent sandalwood Santosa 2015. 2) The results of the t test obtained t count for variable working environment of 2.471 while ttable of 2.006, then Ho is rejected so that there is significant influence among the working environment on the performance of individual employees. 3) The results of the t test obtained t count for the achievement motivation of 2.282 while t table of 2.006, then Ho is rejected so that there is significant relationship between achievement motivation on employee performance is individu.4) F-test analysis results obtained F count = 15.252> Ftabel = 3.23, then Ho is rejected so that together there is significant influence work environment (X1), achievement motivation (X2) on employee performance (Y) .From the results of the analysis of data obtained by the coefficient of determination R2 of 0.379 which indicates that the combination work environment variables and achievement motivation of 37.90%, while 62.10% is influenced by other variables not examined.